Clinical preparation at the middle level : practices and possibilities - Howell, Penny B.; Carpenter, Jan Marie; Jones, Jeanneine P. (Handbook of resources in middle level education., 2016)
This text highlights partnerships between schools and teacher preparation programs where candidates have opportunities to learn in their coursework alongside teachers in the classroom in clinical settings, bridging the theory-practice divide and helping candidates better understand the simultaneous and multi-dimensional nature of teaching and learning in schools. All of the authors in this text describe how their programs go beyond informal arrangements and include a collaborative relationship between the school and university. As a Handbook of Resources, this text provides details about roles, relationships, expectations, organizational structures, and the challenges of partnerships, which will help those who wish to establish a clinically-based model and move confidently from vision to implementation. The authors of the chapters clearly describe the details of their partnerships so their stories can be a resource for others in similar contexts or situations. In doing so, each chapter highlights the different ways to develop partnerships, as well as provides opportunities for universities, schools, and districts with established partnerships to share their stories, wisdom, and expertise and offer inspiration, encouragement, and ideas. The authors of these chapters acknowledge the tensions inherent in the process of developing, implementing, and sustaining an effective, viable partnership by providing insight into how challenges are addressed at different stages of a partnership and what benefits, successes, and differing perspectives exist in this type of relationship.There are a variety of schools represented in this body of work--rural, suburban, private, public, large research intensive, and small private. By design, we believe any school can find themselves in this text as the authors offer suggestions and ideas that can be implemented in other structures. With that said, we want to emphasize that the examples provided are meant to inspire creativity and possibility as programs develop partnerships rather than offer a wholesale approach or a recipe. Viewing the reader as the expert at their institution, this text offers insights into ways to shape the ideas and structures to fit their context.